Interlaboratory study on lipid oxidation during accelerated storage trials with rapeseed and sunflower oil analyzed by conjugated dienes as primary oxidation products - Amft, Jonas (2023)
Accelerated storage tests are frequently used to assess the oxidative stability of foods and related systems due to its reproducibility. Various methods and experimental conditions are used to measure lipid oxidation. Differences between laboratories make it necessary to determine the repeatability and reproducibility of oxidation tests performed under the same conditions. The objective of the present interlaboratory study was to evaluate the outcome of a storage test for two different bulk oils, sunflower oil (SFO) and rapeseed oil (RSO), during a period of 9 weeks at 20°C, 30°C, 40°C, and 60°C. Sixteen laboratories were provided with bottled oils and conducted the storage tests according to a detailed protocol. Lipid oxidation was monitored by the formation of conjugated dienes (CD) and the activation energy (Ea) was determined for comparative purposes and statistically evaluated. An increase in CD formation was observed for both oils when the storage temperature was increased in all laboratories. The Ea,1 ranged from 47.9 to 73.3 kJ mol−1 in RSO and from 27.8 to 62.6 kJ mol−1 in SFO, with average values of 58.2 and 46.8 kJ mol−1, respectively. The reproducibility coefficients were 10.9% and 18.2% for RSO and SFO, respectively. Practical applications: In order to compare results on oxidative stability of foods derived from different studies, the reproducibility of storage tests and methods employed to evaluate the oxidation level should be considered. This study provides fundamental data on the reproducibility of lipid oxidation under accelerated storage conditions and defines important parameters to be considered for the conduction of experiments.